Efektivitas Software Organ Dose Modulation (ODM) dalam Penurunan Dosis Radiasi pada CT Thorax - Fatmayanti, Halinda; Sulaksono, Nanang; Kurniawati, Ary (Jurnal Imejing Diagnostik (JImeD), 2026)
Background: CT Scanning is a diagnostic examination modality that uses radiation to obtain detailed cross-sectional images of the human body. CT thorax is a frequently performed examination to evaluate lung parenchyma, airways, and mediastinal structures. This increases collective radiation exposure, thereby increasing long-term biological effects, especially on radiosensitive organs in the thorax, such as the mammary glands, thyroid, lungs, and spinal cord. One strategy to optimize dose exposure to radiosensitive organs is to use Organ Dose Modulation (ODM) software. ODM is a CT feature that can reduce radiation exposure to radiosensitive organs. This study aims to evaluate the effectiveness of ODM in reducing radiation dose in CT thorax examinations and its impact on image quality. Methods: This experimental study using a quantitative approach was conducted by Scanning a torso phantom from August to October 2025 at Indriati Solo Baru General Hospital. Thoracic Scanning was performed with two conditions: ODM OFF and ODM ON. Radiation exposure measurements in radiosensitive areas were performed by placing TLDs over the thyroid, mammary glands, lungs, and vertebrae (spinal cord), with each measurement repeated twice. Image quality was then assessed using SNR and CNR measurements with three repeated measurements. The resulting data were analyzed descriptively and analytically to compare dose distribution and image quality when the ODM was turned off and on. Results: TLD measurements demonstrated dose redistribution when the ODM was activated. Comparison of the average dose showed a decrease in anterior radiosensitive organs, with a 2.59% decrease in the thyroid and a 16.71% decrease in the mammary glands. Conversely, there was an increase in dose in the posterior and lateral regions, with a 45.05% increase in the vertebrae and a 5.05% increase in the lungs. Image quality analysis revealed a 14.76% increase in SNR and a 28.30% increase in CNR when the ODM was activated. Conclusions: This study demonstrates that the ODM not only reduces radiation dose to anterior radiosensitive organs but also improves image quality.